The Application of the Principle of Collaborative Governance in the Management of Beggars, Homeless People, and the Displaced (PGOT) in the City of Cirebon - Zahratun Nazieha; N Nursahidin (CV. Media Digital Publikasi Indonesia, 2026)
PGOT refers to beggars, vagrants, and the impoverished, recognized as marginalized groups reliant on public spaces for survival. This research investigates the use of collaborative governance principles in managing PGOT in Cirebon city. Utilizing a descriptive qualitative methodology with a case study approach, the study focuses on documenting, analyzing, and interpreting the relevant phenomena. Data analysis is grounded in the Collaborative Governance theory by Chris Ansell and Alison Gash (2008), particularly in relation to local government agencies such as the Population and Civil Registration Office (Disdukcapil), the Health Department, the Social Affairs Department, and the Public Order Agency (Satpol PP). The findings reveal that while initial collaboration among local government agencies exists, it is primarily sectoral, ad hoc, and lacks sustainable integration. Institutional design is bolstered by a solid legal framework established through Local Regulation No. 13 of 2019, along with Memorandums of Understanding between agencies; however, these have not yet led to comprehensive collaborative services. In terms of facilitative leadership, there is a lack of effective collaborative leadership that allocates value, as leaders' roles are limited to formal coordination. Although trust and commitment among stakeholders have been fostered, collaboration remains selective and conditional, primarily responding to PGOT during enforcement operations or emergency situations. Major challenges include limited financial resources, weak regulatory enforcement, and persistent reliance on street-based livelihoods, while opportunities for strengthening collaboration lie in the engagement of social partners, the utilization of digital governance, and community-based preventive approaches.